2016
DOI: 10.1111/cch.12333
|View full text |Cite
|
Sign up to set email alerts
|

Rates of detection of developmental problems at the 18‐month well‐baby visit by family physicians' using four evidence‐based screening tools compared to usual care: a randomized controlled trial

Abstract: Despite higher early detection rates in the evidence-based care group, there were no differences in referral rates between evidence-based and usual-care groups. This suggests that clinicians: (1) override evidence-based screening results with informal judgment; and/or (2) need assistance understanding test results and making referrals. Possible solutions are improve the quality of information obtained from the screening process, improved training of physicians, improved support for individual practices and acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 28 publications
0
25
0
4
Order By: Relevance
“…Studies have suggested that without using evidence-based assessment methods practitioners may have greater difficulties detecting mild delays or suspected deviations compared to not using an evidence-based assessment method[16,40,6870]. A Swedish study reported that the average age for referral of children with CP from the CHS to rehabilitation services was 12 months[69].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have suggested that without using evidence-based assessment methods practitioners may have greater difficulties detecting mild delays or suspected deviations compared to not using an evidence-based assessment method[16,40,6870]. A Swedish study reported that the average age for referral of children with CP from the CHS to rehabilitation services was 12 months[69].…”
Section: Discussionmentioning
confidence: 99%
“…To facilitate early detection of motor problems and developmental delays the use of standardized assessment methods is recommended[2,10,16]. Not only does assessment using standardized methods improve the accuracy of detection, it also provides valuable information compared to clinical judgment alone[1619].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…U 25 porodica procjena ranog razvoja vršila se "neformalno", a u 29 slučajeva upotrebom upitnika za čije popunjavanje nije trebalo više od 10 minuta. U prvoj grupi identifikovano je 4 % , a u drugoj 62 % djece sa mogućim razvojnim problemima (13).…”
Section: Rezultatiunclassified